Identifying relationship of lipid profile with hypertension among diabetic patients - Alamgir, Muhammad Ahmed; Alamgir, Irum; Aqil, Shafique; Ali Qazi, Masroor; Imran, Ali; Aslam, Javeria; Hassan, Humanyun (International Journal of Endorsing Health Science Research, 2018)
Background: Relevant literature suggests that hypertension (HTN) is commonly linked with lipid abnormalities among diabetics so management of dyslipidaemia may reduce the cardiovascular complications significantly. The study was aimed to evaluate whether dyslipidaemia was associated with HTN among type 2 diabetics. Methodology: This hospital-based, observational, retrospective and comparative study was carried out from January 2018 to June 2018 in the medical outdoor department of Bahawal Victoria Hospital (BVH), Bahawalpur. The study sample was comprised of 50 normotensive diabetic patients as control (group A) and 50 diabetic subjects with HTN were labeled as group B. Comparative values of lipids were primarily observed between the two groups. Quantitative demographic data, blood pressure (BP) recordings, laboratory values of lipid and serum sugar levels were presented as percentage, mean and standard deviation accordingly. To determine statistical assessment, Statistical Package for the Social Sciences (SPSS) version 15 was used and Student t-test was applied to compare the means of two groups for lipoproteins with significance level at 5%. Results: Analytic results of this study showed that hypertensive subjects (group B) had hyperlipidemia along with uncontrolled hyperglycemia as well. Among them, high-density lipoprotein cholesterol (HDL- C) was 32.73±4.47mg/dl while in normotensive control (group A) it was 39±2.94 mg/dl. Same with the total cholesterol (TC) and triglycerides (TG), both lipoproteins were observed in greater concentrations among hypertensive patients as 194.68±31.75mg/dl and 196.05±78.45mg/dl respectively, compared to control (179.07±38.61mg/dl and165.75±48.80mg/dl respectively). Hyperlipidaemia was defined according to guidelines for diabetic patients provided by the National Cholesterol Education Program /American Diabetes Association (NCEP/ADA). Conclusion: It can be concluded from the study results that diabetics having HTN have more susceptibility towards hyperlipidemia when compared to the normotensive diabetic.